Effects of Difenoconazole and Imidacloprid Seed Coatings on Soil Microbial Community Diversity and Ecological Function - Dunfeng Feng; Jiabin Chen; Guo Li; Xiaoying Yang; Yujie Xiong; An Lao; Suzhen Huang; Zheng Zheng (Microorganisms)
Difenoconazole and imidacloprid are key components of seed-coating agents, which alter soil microbial community structure and function after application. Existing studies mainly focus on the environmental effects of their spraying application, while research on their impacts on the soil ecosystem when used as seed-coating agents is relatively limited. Through field experiments, this study systematically evaluated and compared the effects of difenoconazole and imidacloprid seed coatings on wheat rhizosphere soil microbial communities and ecological functions by measuring soil enzyme activities, employing 16S rRNA and ITS high-throughput sequencing technologies and predicting KEGG functional pathways. The results showed that imidacloprid and difenoconazole significantly reduced bacterial community diversity, particularly under the high-dosage difenoconazole treatment (0.18 g a.i./kg seed), with a 5.80% decrease in diversity by day 30. This treatment most strongly inhibited the phyla Bacteroidota and Myxococcota, with maximum reductions of 23.87% and 63.57%, respectively. However, the abundance of Actinobacteriota significantly increased, with a maximum increase of 38.53%. Additionally, fungal community diversity significantly increased under both difenoconazole and imidacloprid treatments. Both seed coatings significantly altered the microbial community structure from days 20 to 60, with recovery occurring by day 120. Furthermore, KEGG pathway analysis revealed that the high-dosage difenoconazole treatment (0.18 g a.i./kg seed) significantly activated functional pathways such as cell motility, signal transduction, and membrane transport, whereas the standard dosage (0.12 g a.i./kg seed) exhibited metabolic suppression. This study elucidates the dynamic impacts of seed-coating agent application on soil microbial communities, providing theoretical support for rational pesticide use and the optimization of agricultural strategies.